(untitled) (Baghdad Science Journal, 2017)
In the current study, synthesis and characterization of silver nanoparticles (AgNPs) before and after functionalization with ampicillin antibiotic and their application as anti-pathogenic agents towards bacteria were investigated. AgNPs were synthesized by a green method from AgNO3 solution with glucose subjected to microwave radiation. Characterization of the nanoparticles was conducted using UV-Vis spectroscopy, scanning electron microscopy (SEM), zeta potential determination and Fourier transform infrared (FTIR) spectroscopy. From SEM analysis, the typical silver nanoparticle particle size was found to be 30 nm and Zeta potential measurements gave information about particle stability. Analysis of FTIR patterns and UV-VIS spectroscopy confirmed the production of nanosilver particles. The activity of produced silver NP was tested against three pathogens (Escherichia coli, Staphylococcus aureus, and Acinetobacter baumannii) in both liquid and solid growth medium. AgNPs presented potential antibacterial activity, against tested bacteria. Ag and Ag-AMP nanoparticles were detected to have penitent antimicrobial. The optical density (OD) of the culture solution and measuring zones of inhibition were used to monitor the growth of bacteria in liquid and solid growth medium respectively